2021
DOI: 10.3389/fnsys.2021.596221
|View full text |Cite|
|
Sign up to set email alerts
|

Changes in Resting-State Functional Connectivity of Cerebellum in Amnestic Mild Cognitive Impairment and Alzheimer’s Disease: A Case-Control Study

Abstract: This case-control study is aimed to investigate the correlation of altered functional connectivity (FC) in cerebellum with cognitive impairment in amnestic mild cognitive impairment (aMCI) and Alzheimer’s disease (AD). The morphometric and resting-state FC MRI analysis including 46 participants with AD, 32 with aMCI and 42 age-matched normal controls (NCs) were conducted. We compared the cerebellar gray matter volume and cerebellar FC with cerebral cortical regions among three groups. To investigate the relati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…But it has received little investigation in the pathophysiology of AD, as historically the cerebellum has been studied for its role in the regulation of motor activity. However, recent studies have shown a role for the cerebellum in cognition, including roles in working memory and executive and visuospatial functions [18][19][20].…”
Section: Plos Geneticsmentioning
confidence: 99%
See 1 more Smart Citation
“…But it has received little investigation in the pathophysiology of AD, as historically the cerebellum has been studied for its role in the regulation of motor activity. However, recent studies have shown a role for the cerebellum in cognition, including roles in working memory and executive and visuospatial functions [18][19][20].…”
Section: Plos Geneticsmentioning
confidence: 99%
“…The presence of the rs10423769_A allele reduces the odds ratio for Alzheimer disease risk from 7.2 for ApoE ε4/ε4 carriers lacking the A allele to 2.1 for ApoE ε4/ε4 carriers with at least one A allele. This locus is located approximately 2 mB upstream of the ApoE locus, in a large cluster of pregnancy specific beta-1 glycoproteins on chromosome 19 and lies within a long noncoding RNA, ENSG00000282943. This study identified a new African-ancestry specific locus that reduces the risk effect of ApoE ε4 for developing Alzheimer disease.…”
mentioning
confidence: 99%
“…These ndings align with prior research that has indicated the potential for high classi cation accuracy in structural or functional imaging of these regions. They underscore that these connectivity alterations represent a promising and reliable candidate for a useful signature in the context of AD [6, 7,14,15,20,[51][52][53][54][55]. Notably, several nodes were situated in the DMN, whose impaired connectivity had been consistently identi ed as a robust biomarker of cognitive disorder.…”
Section: Discussionmentioning
confidence: 99%
“…The cerebellum's involvement in processing various cognitive functions such as working memory [8],emotion [9], language [10], and other executive functions [11] is likely attributable to its extensive connections with cortical regions [12]. Additionally, alterations in functional connectivity (FC) are evident in the preclinical stages of AD [13][14][15]. The thalamus is a subcortical structure closely linked to the cerebellum, and their interactions play crucial roles in cognitive functions.…”
Section: Introductionmentioning
confidence: 99%
“…A recent FC study on AD and MCI subjects elucidated a possible interaction of ventral attention network and cerebro-cerebellar limbic network as functional compensation in MCI [78]. Moreover, changes of cerebro-cerebellar FC were closely correlated with cognitive subdomains in AD and aMCI [79], and aMCI subjects demonstrated lower anti-correlation between cerebro-cerebellar and DMN FC [80]. Further, when compared with HC and MCI patients, AD patients exhibited significantly decreased dynamic amplitude of low-frequency fluctuation variability in the cerebellum and temporal lobes [81].…”
Section: Group By Regional Suvr Interactions In Cerebro-cerebellar Networkmentioning
confidence: 96%